2003
DOI: 10.1073/pnas.0438019100
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism converting psychosocial stress into mononuclear cell activation

Abstract: Little is known about the mechanisms converting psychosocial stress into cellular dysfunction. Various genes, up-regulated in atherosclerosis but also by psychosocial stress, are controlled by the transcription factor nuclear factor B (NF-B). Therefore, NF-B is a good candidate to convert psychosocial stress into cellular activation. Volunteers were subjected to a brief laboratory stress test and NF-B activity was determined in peripheral blood mononuclear cells (PBMC), as a window into the body and because PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
542
1
27

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 814 publications
(602 citation statements)
references
References 61 publications
12
542
1
27
Order By: Relevance
“…A CSD study in BALB/c CSD mice and C57BL/6 aggressor mice also reported increased plasma levels of TNF and proinflammatory interleukins; although the standard CSD protocol was used there were no correlations between cytokine level and number of bite wounds received (Savignac et al, 2011a). In healthy humans, acute psychosocial stress causes increased blood levels of pro-inflammatory cytokines (Bierhaus et al, 2003) and blood levels of TNF and IL-6 are increased in depression (Dowlati et al, 2010). In addition, the spleens of CSD mice were hypertrophic, consistent with invasion and expansion of activated immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…A CSD study in BALB/c CSD mice and C57BL/6 aggressor mice also reported increased plasma levels of TNF and proinflammatory interleukins; although the standard CSD protocol was used there were no correlations between cytokine level and number of bite wounds received (Savignac et al, 2011a). In healthy humans, acute psychosocial stress causes increased blood levels of pro-inflammatory cytokines (Bierhaus et al, 2003) and blood levels of TNF and IL-6 are increased in depression (Dowlati et al, 2010). In addition, the spleens of CSD mice were hypertrophic, consistent with invasion and expansion of activated immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms mediating the adverse effect of stress on CVD risk include exaggerated or dysregulated immune activation in response to psychosocial stress [1,3]. Acute mental stress elicited using behavioral or cognitive tasks is known to up-regulate pro-inflammatory gene expression in peripheral mononuclear blood cells resulting in the synthesis and release of inflammatory cytokines [4,5]. Evidence shows that the binding activity of the nuclear factor-kappaB (NF-kB), a key mediator of inducible transcription in the immune system and inflammatory genes, is enhanced by exposure to acute stress in humans.…”
mentioning
confidence: 99%
“…Evidence shows that the binding activity of the nuclear factor-kappaB (NF-kB), a key mediator of inducible transcription in the immune system and inflammatory genes, is enhanced by exposure to acute stress in humans. This is likely mediated through adrenergic receptor stimulation [4,6,7] and appears to be inversely related to glucocorticoid responses [7,8].…”
mentioning
confidence: 99%
“…Psychological stress promotes NF-κB activation, providing a channel for translating psychological stress into mononuclear cell activation 22 . In contrast, two key omega-3 PUFA, eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA), can substantially decrease lipopolysaccharideinduced (LPS-induced) TNF-α expression by blocking NF-κB activation 21 .…”
Section: Diet and Inflammationmentioning
confidence: 99%